Pengaruh Efikasi Diri Dan Lingkungan Kerja Terhadap Kepuasan Kerja Karyawan - Utami Puji Lestari; Ella Anastasya Sinambela; Rahayu Mardikaningsih; Didit Darmawan (LPPM Sekolah Tinggi Ilmu Ekonomi Al-Washliyah Sibolga, 2020)
Human resource development is take carried out in the journey with the times. This development is carried out so that the company's goals can be accomplished and the company is able to stayed for a long time. The dirrection of this reserach was to determine the aspect of self-efficacy and work environment on employee job satisfaction. The population of this study are employees at a company in Sidoarjo. The sample with was 133 respondents with the census technique. Multiple linear regression is the data analysis used.. The results obtained are self-efficacy partially significant effect on employee job satisfaction. The work environment has a significant effect on employee job satisfaction. Self-efficacy and work environment have an effect on job satisfaction simultaneously